Exploring the determinants of career success after expatriation: a focus on job fit, career adaptability, and expatriate type - Mello, Rodrigo; Suutari, Vesa; Dickmann, Michael (Taylor & Francis, 2024)
Expatriation significantly influences the career paths of individuals after their international work experience. This study draws on person-environment fit and career construction theories to examine the role of job fit, career adaptability, and expatriate type in shaping both objective and subjective career success. Our 2020 sample comprised 191 expatriates who had worked abroad four to five years prior. This group included both self-initiated and assigned expatriates, as well as repatriates and re-expatriates, providing a broader scope than is typical in expatriation studies. The research reveals that job fit, career adaptability, and expatriate type substantially affect career outcomes. It also identifies that the type of expatriate moderates the relationship between career adaptability and objective career success. Our work extends the applicability of person-environment fit theory and career construction theory within the complex landscape of expatriate careers. The investigation not only deepens our understanding of the factors driving career success post-expatriation but also provides valuable insights to aid the effective management of international careers.
Keywords: Expatriation; career success; proactive behaviour; job fit; career adaptability; repatriation; re-expatriation